Imam al-Ghazali dan Ilmu Hadits: Beberapa Pernyataan dan Tanggapannya - Muhammad Ardiansyah (Adabuna : Jurnal Pemikiran dan Pendidikan, 2022)
This paper addresses a theme that is still being discussed to this day.  That is about the authority of Imam al-Ghazali in the science of Hadith. There are debates among al-Ghazali's scholars and reviewers. There are five factors that are the background for the presence of criticism of the Hujjatul Islam. Through this paper the author seeks to position the problem fairly. The author uses qualitative methods with historical analysis, content analysis and comparative analysis. The results of the author's study have several conclusions. First, criticism of al-Ghazali has been going on for a long time, not new today. Second, Some of the criticisms made against al-Ghazali are true. Third, Some of the criticisms are not entirely correct and need to be addressed fairly based on existing data. Fourth, based on this study the author states that al-Ghazali is a scholar who has authority in the science of hadith Dirâyah and Ma'âni al-Hadîts, although it is not known as Muhaddits in Riwâyah among scholars. At least in terms of Dirâyah and understanding of hadith, al-Ghazali is still more authoritative than the scholars of his time, as well as compared to the scholars or hadith reviewers of this era.